Successful Smoking Cessation by Moderate Smokers: A Case Series - Tiranda, Yulius; Yudi Abdul Majid (Caring: Indonesian Journal of Nursing Science, 2025)
Indonesia is one of the countries with the largest smoking population worldwide, and remains the only ASEAN nation that has not ratified the Framework Convention on Tobacco Control (FCTC). This has led to the continuous increase in catastrophic diseases recorded every year. Meanwhile, the role of health workers, specifically nurses, is very crucial in reducing smoking behavior. Cessation is a surefire strategy to start improving public health and the environment, although the initial steps are very difficult for active smokers. Therefore, effective programs and strategies consistent with individual motivation and cultural contexts are needed to achieve optimal smoking cessation outcomes. Three active moderate smokers aged 20, 21, and 45 years followed the programs and strategies provided for 3-6 months. The results showed smoking cessation was successfully achieved. The strategies adopted, namely Self Awareness, Sounding, and Support Systems, have the potential to successfully achieve smoking cessation. The process requires a personal approach and knowledge about possible motivations, as well as smokers culture to function properly. Furthermore, strengthening is also needed as a support system to prevent a relapse.